Flexible nanocomposite electrode materials for energy applications - Muhammad Nurhisyam Sahul Hameed (2014)
Carbon nanotubes (CNTs) hold the potential of providing exceptional mechanical properties and other functional characteristics. There have been continuous efforts to develop dispersion and functionalization techniques to deploy carbon nanotubes as effective reinforcement in polymer nanocomposites. This paper reviews the comparison of different conventional modification techniques for multi-walled carbon nanotubes (MWCNTs) in achieving improved mechanical strength without compromising flexibility in fabricating a nanocomposite thin film. In addition, carbon black or Chinese ink was incorporated into the nanocomposite as fillers which were able to promote mechanical enhancement, electrical conductivity and thermal conductivity. In this work, the multi-walled carbon nanotubes were functionalized by acid treatment and ball-milling to attain better dispersion and promote interfacial interactions between the fillers and the polymer matrix. The tensile tests showed that addition of modified MWCNTs result in increased Young’s Modulus. Fourier Transform Infrared Spectroscopy showed that modified MWCNTs promote interfacial bond formations with the polymer matrices. The Differential Scanning Calorimetry and Thermogravimetric Analysis measurements also showed improved thermal properties such as increase in glass transition temperature (Tg) and decomposition temperature. For future research, it is recommended to improve on the processing techniques of casting and drying of the nanocomposite film to achieve better mechanical results.